A combined multipulse-multilevel inverter based STATCOM for improving the voltage profile and transient stability of power system. (4th March 2009) - Geethalakshmi, B.; Dananjayan, P.
In this paper, a new combined multipulse-multilevel inverter topology is proposed for static synchronous compensator to regulate AC supply voltage at a constant level. A detailed analysis of the operating characteristics of the various inverter topologies in respect of total harmonic distortion (THD) and device count are compared in the paper. A closed loop decoupled control strategy for operating the STATCOM in the automatic voltage control mode is proposed. To analyse the performance of the STATCOM connected in shunt with the transmission line, a single machine infinite bus power system has been considered. The complete digital simulation of the STATCOM incorporated into the power system is performed in the MATLAB/simulink environment and the results are presented to validate the feasibility of the proposed topology.